Response and tolerance ability of Chlorella vulgaris to cadmium pollution stress - Geng, Weiwei (Environmental technology, 2022)
Cadmium, which is widely used in electroplating industry, chemical industry, electronic industry and nuclear industry, is harmful to human health and ecological environment. The effects of Cd at different initial concentrations on biomass, antioxidant enzyme activity and ultrastructure of Chlorella vulgaris were analysed in the present study. The results showed that C. vulgaris maintained a slow-growth trend at 3.0 mg/L Cd, and the peroxidase (POD) enzyme activity reached the highest at this concentration, which indicated that C. vulgaris could resist the oxidative damage of cells by increasing the enzyme activity, so as to improve the tolerance of C. vulgaris to Cd. When the concentration of Cd was 5.0 mg/L, although the activity of the superoxide dismutase enzyme was still very high, POD enzyme could not remove the hydrogen peroxide produced in cells in time, leading to cell damage and even death. Therefore, when the concentration reached 5.0 mg/L, the growth of C. vulgaris began to decline after four days of stress, and the cell structure was significantly damaged after six days of stress. And the higher concentration of Cd caused more Cd accumulation in cells and a serious damage to C. vulgaris. C. vulgaris can be used as an early warning indicator of Cd pollution, and it can be used for bioremediation of Cd contaminated water through tolerant subculture